THE NEW WORLD ORDER AND ITS IMPLICATIONS FOR THE FUTURE OF NATIONS - Mourad Belkaid Abdi; Abdellah Abdellaoui (International Journal of Innovative Technologies in Social Science, 2025)
The New World Order emerged as an inevitable consequence of the post-Cold War era, which ended with the collapse of the Eastern Bloc represented by the Soviet Union. In response, the United States sought an alternative focus—namely, the fight against terrorism. To achieve its strategic interests, the U.S. adopted the New World Order, officially declared by former President George H.W. Bush during his war on terrorism, which he initiated with the invasion of Iraq. The U.S. prioritized its national security above all else, often at the expense of state sovereignty, by imposing conditional protection under the pretext of democracy and human rights. This approach enabled the U.S. to dominate the world and its institutions, particularly with Israel situated at the heart of the Middle East, where America exerts global influence in the name of protecting peace and ensuring maritime security.